(untitled) (Texas Journal of Medical Science, 2024)
Dental prosthetics on artificial implant supports most effectively provides the patient with chewing function, anatomical and physiological structure close to the norm, and, consequently, professional and social status necessary for confidence in society. However, the achieved successes in dental implantation do not solve the issues of reducing complications after implant treatment and increasing the terms of use of implants. Great difficulties in the success of the implantation process are associated with background and somatic diseases.